Narrating Cultural Heritage - Ulf Palmenfelt (Journal of Ethnology and Folkloristics)
In this article, I investigate some of the elements and mechanisms involved in the process in which cultural heritage, in the form of narrated local history, emerges. My argumentation is that certain collectively known phenomena achieve such a strong agency of their own that they have the power to force themselves into individuals’ life histories. In analogy with Albert Eskeröd’s concept dominant of tradition, I suggest that these elements from local and national history be called dominant units. The interplay between several individual narratives in a local community and the collective elements takes the form of a joint negotiating process, generating agreements and discrepancies, shared ‘truths’ and contested disagreements, the acceptance of shared local symbols and the forgetting of less captivating material. The emerging products of such processes are grand narratives in different degrees of development circulating at different levels and in different cultural arenas in a community.